Trade and the environment : fundamental issues in international law, WTO law, and legal theory - Vranes, Erich (Oxford : Oxford University Press, 2009)
The relationship between WTO law and international and domestic efforts to protect the environment is a central concern in WTO and international environmental law. These issues are analysed here by examining the fundamental provisions of WTO law and exploring its interaction with general international law and national law.
Includes bibliographical references and index.
Description based on print version record.
Keywords: World Trade Organization; Environmental law, International; Foreign trade regulation; International trade -- Environmental aspects